Framework for Green School Model Development in Malaysia - Karunakaran, Sivasanghari; Verayiah, Renuga (International Journal of Engineering and Technology, 2018)
In parallel to global modernization especially in developing country like Malaysia, the urging for energy consumption conservation unwaveringly increases. The initiative of implementing the green building concept and practices is being developed to promote the sustainable development of global society at many levels. Green school model is among the initiatives being explored in this paper. In Malaysia, currently there is no significant studies or guidelines have been developed for green school model development. Thus, the aim of this paper is to review and analyze the requirement for green school model establishment which ultimately will act as a guideline for the implementation of green school model in Malaysia. To achieve this, study on general rules adopted to assess the green school model development by various countries is ventured. In particular, the focus is based on the energy efficiency, water efficiency, thermal comfort, indoor air quality, lighting efficiency, visual health, acoustics, and space utilization. The challenges for the development of green school model in Malaysia is also highlighted. Detailed review on the recent Malaysia’s policies and energy development plan is presented. The outcome of this study is a framework for green school model development in Malaysia addressing one of the prime key subject which is the lighting efficiency and its impact towards students’ performance.